Association of Antiretroviral Regimens and CD4 Counts with Dyslipidemia in HIV Patients: Implications for Metabolic Management - Rosandy, Milanitalia Gadys; Candradikusuma, Didi; Yudha, Nyoman Satvika Dharma (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Dyslipidemia, a key risk factor for cardiovascular disease, is prevalent among people living with HIV/AIDS receiving antiretroviral therapy. This study aims to evaluate the impact of different ART regimens on lipid profiles in HIV patients and identify regimens with better outcomes in lipid profile levels. Subjects and Method: An observational study was conducted from June to August 2024 at Dr. Saiful Anwar Regional General Hospital, Malang, Indonesia. Participants were recruited using consecutive random sampling, including HIV patients on ART for at least three months. Independent variables included ART regimens and CD4 counts, while the dependent variable was dyslipidemia status. Data were collected via demographic forms, medical record reviews, and lipid profile analysis. Statistical analysis was performed using chi-square and t-tests, with significance set at p < 0.05. Results: Of the 110 participants, 38.2% were identified with dyslipidemia. The highest dyslipidemia rates were observed in patients using the Duviral Alluvial regimen (80.0%), followed by Duviral Neviral (71.4%). Newer regimens, TLD and TLE, were associated with lower dyslipidemia rates (31.3% and 36.0%, respectively; p = 0.045). A significant association was also noted between dyslipidemia and CD4 counts, with dyslipidemic patients showing higher mean CD4 counts (560.29 cells/μL) compared to non-dyslipidemic individuals (378.40 cells/μL; p = 0.009). Conclusion: Newer ART regimens such as TLD and TLE are associated with better lipid profile outcomes and lower dyslipidemia risk compared to older regimens. Higher CD4 counts may reflect an increased risk of lipid abnormalities, emphasizing the need for lipid monitoring and regimen optimization in HIV care.